ANALISIS KEBUTUHAN KOMUNITAS UNTUK KESIAPSIAGAAN MASYARAKAT PADA ASPEK KESEHATAN MENGHADAPI BENCANA BANJIR BANDANG DI AFDELING GUNUNG PASANG, DESA SUCI, KECAMATAN PANTI, KABUPATEN JEMBER - Dhyani Ayu Perwiraningrum; Rahmat Hidayat; Fatwa Sari Tetra Dewi (Jurnal Permata Indonesia, 2017)
Preparedness is an important steps in efforts to disaster risk reduction on vulnerable communities. Afdeling Gunung Pasang classified as disaster-prone areas in flashflood, so that the community requires preparedness. To develop the necessary preparedness in community it needs analysis. The analysis includes assessing felt needs and fulfillment of normative needs, especially in the aspect of health for disaster risk reduction. In Indonesia, there are several criteria for fulfilling the health needs of disaster include the provision of clean water and sanitation, foods and clothing, health services, psychosocial services andshelters.Purpose: The main objective of this study for knowing about the community needs to develop a community preparedness in health by felt needs and fulfillment normative needs to prevent flashflood disaster in Afdeling Gunung Pasang, Suci Village, Panti Sub-Regency, Distric of Jember Method: This was a qualitative study with phenomenological approach. The main informan were community of Afdelling Gunung Pasang as well as, supporting informan were leaders of community, head of village office, stakeholder of community (Perusahaan Daerah Perkebunan) and stakeholder of disaster management (intitution of local government) in District of Jember. The main informan for focus group discussion were determined with purposive technique. Data collecting by focus group discussion, in depth interview, and observation. To validate the data was bytriangulation method and source. Findings: Many kind of felt needs finding in community to develop a community preparedness in health. Study by social representation of community experience in disaster, community needs stimulus such as training emergency response, fulfillment tools, disaster information and coordination with stakeholder. The needs aims to health prevention and observing dangerous zone in Afdeling Gunung Pasang.